The Role of IL-7/IL-7R Signalling in Thymic Dysfunction in HIV-1 infection - Young, Charlene Donna (Université d'Ottawa / University of Ottawa, 2011)
Immune reconstitution following T-cell depletion consists of expansion of circulating T-cells or de novo synthesis of T-cells from the thymus. The IL-7/IL-7 receptor signalling pathway is critical for the maturation and differentiation of thymocytes before they leave the thymus as mature T-cells. Viral infections including HIV have been shown to decrease IL-7Ralpha (CD127) expression on circulating CD4+ and CD8+ T-cells. However little is known about the effects of HIV infection on CD127 expression and activity in thymocytes despite existing evidence of HIV infection of the thymus. Thymic function is altered in HIV infection leading to a dysregulation of the thymic epithelial network and reduced thymic output which may contribute, in part, to impaired immune reconstitution in progressive HIV disease. In vitro studies demonstrate that HIV infection interrupts thymopoiesis resulting in a developmental block in thymopoiesis similar to that seen in models of IL-7/IL-7R deficiencies suggesting a role for altered IL-7 signalling in HIV associated thymic dysfunction. Therefore we hypothesize that thymic dysfunction which occurs in HIV infection is due to reduced IL-7R and/or altered IL-7 signalling in thymocytes resulting in impaired de novo T-cell synthesis. In order to address this hypothesis an in vitro system for the functional study of human thymocytes has been optimized. The research conducted as part of this thesis assessed if in vitro HIV infection or if cytokines that are upregulated in the course of HIV infection altered CD127 expression on maturing thymocytes. It also evaluated if in vitro HIV infection disrupts thymocyte function at different stages of maturation and whether this disruption in function is due to impaired IL-7/IL-7R signalling. The host factors IL-7, TNF- and IL-4, which are upregulated in HIV infection, are found to downregulate CD127 expression on thymocytes. IL-4 pre-treatment of thymocytes reduced the ability of IL-7 to induce STAT-5 phosphorylation. Furthermore following in vitro HIV infection of thymocytes, CD127 expression of single positive CD8 thymocytes was decreased. In vitro HIV infection altered IL-7 activity as demonstrated by lower levels of Bcl-2 and phospho-STAT-5 expression in thymocytes following IL-7 stimulation. These accumulated results suggests that HIV may play a role in impaired thymic function by altering IL-7 responsiveness. Understanding the mechanisms of thymic dysfunction in HIV infection may provide some insight into therapies leading to immune reconstitution through increased thymic output.
Keywords: Thymocytes; IL-7; CD127; HIV